A packet scheduler with forward equilibrium and adaptive fair selection method in wireless multimedia traffic environment - Kunmin Yeo; Byung-Han Ryu; Soon-Young Lim (2003 International Conference on Communication Technology : ICCT2003 : proceedings : April 9-11, 2003, Beijing, China, 2003)
In this paper, a self-adaptive algorithm of a packet scheduler is addressed as a crucial method of high-speed transmission of multimedia traffic in a shared wireless link, in accordance with new architectural functions. In the slot budget that is updated sequentially in the order of priorities of applications and sessions, adaptive modulation and coding options are considered to take into account radio links subject to fading and interference. The dedicated local packet scheduler that is in control of each type of application employs an application-sensitive scheduling algorithm. For real-time scheduler, the forward-equilibrium algorithm is introduced to consider the future state of delay. When it comes to non real-time scheduler, the adaptive-fair-selection algorithm is developed to provide the fairness between sessions. The global packet scheduler manages the overall operation of the dedicated local packet schedulers and supervises the slot budget in each transmission-time-interval making a final decision. The scheduler can provide the local fairness between sessions in each service class. Related to the bounds on delay, real-time sessions can be served with predefined requirements at the cost of increased packet dropping rates. Implementation complexity is thought to be simple, providing a low-complexity algorithm in the local scheduler for the nonreal-time class.